PKM Penyuluhan tentang Pencegahan Tindakan “Bullying” terhadap Anak di SDN Sumber Duren Kecamatan Krucil Kabupaten Probolinggo - Islahuddin, Muhmammad; Naufal, Ahmad Wafy; Syafakhorrahman, Moh; Riskiawan, Putra; Ridwan, Moh Bagus (Lembaga Yasin AlSys, 2024)
Bullying is an issue that cannot be overlooked. It is a “sensitive problem” that impacts the development of children/students and is categorized as child delinquency, with cases that seem never-ending. One of the government's efforts to prevent and address juvenile delinquency is by implementing the Juvenile Criminal Justice System through Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, which replaced Law No. 3 of 1997 on Juvenile Courts. However, the solution offered by the government, according to the author, should be avoided in addressing bullying issues, as it may affect the child's mental well-being in the long term. The method used in this study consists of several stages, including preparation, implementation, evaluation, and reflection. The program begins with delivering material, followed by training students to become anti-bullying agents, allowing the students themselves to promote and spread positive behavior to their peers, particularly in reducing bullying behavior. The results of this outreach program show that it was highly beneficial for the students, as they gained a wealth of new knowledge during the activities. This includes understanding the definition of bullying from a legal perspective in Indonesia, various forms of bullying against children, several factors causing bullying incidents, and steps or efforts to tackle bullying.